3-Phosphoglycerate Dehydrogenase Deficiency: Description of Two New Cases in Tunisia and Review of the Literature - Kraoua, Ichraf; Wiame, Elsa; Kraoua, Lilia; Nasrallah, Fehmi; Benrhouma, Hanen; Rouissi, Aida; Turki, Ilhem; Chaabouni, Habiba; Briand, Gilbert; Kaabachi, Naziha; Schaftingen, Emile Van; Gouider-Khouja, Neziha (Neuropediatrics, 2013)
3-Phosphoglycerate dehydrogenase (3-PGDH) deficiency is a rare autosomal recessive disorder of serine biosynthesis. It is typically characterized by congenital microcephaly, intractable seizures of infantile onset, and severe psychomotor retardation. Diagnosis is suspected on decreased l-serine levels in plasma and cerebrospinal fluid (CSF) and confirmed by genetic study. Early diagnosis in index cases allows supplementation in serine and prevention of fixed lesions. Prenatal diagnosis and genetic counseling allows prevention of secondary cases. We report on the two first unrelated Tunisian families with 3-PGDH deficiency confirmed by biochemical and genetic study. We discuss clinical, biochemical, imaging, electroencephalographic, and therapeutic aspects and review the literature.
Keywords: serine; epilepsy; microcephaly; supplementation